2021
DOI: 10.1016/j.adro.2021.100759
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity After Stereotactic Body Radiation Therapy for Prostate Cancer in Patients With Inflammatory Bowel Disease: A Multi-institutional Matched Case-Control Series

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Moreover, a control-matched review of 39 males with inactive IBD who were treated with prostate SBRT showed that IBD was not associated with increased odds of late​ grade ≥​2 GI or GU toxicity (median follow-up time ​of ​89 months). There was, however, an increased acute risk of low-grade GI/GU toxicity in those with dormant IBD [ 23 ]. This data offers encouraging insight into the outcomes of those who received radiation with dormant IBD; however, it is still generally recommended to avoid pelvic radiation, if possible, during an acute IBD flare-up.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a control-matched review of 39 males with inactive IBD who were treated with prostate SBRT showed that IBD was not associated with increased odds of late​ grade ≥​2 GI or GU toxicity (median follow-up time ​of ​89 months). There was, however, an increased acute risk of low-grade GI/GU toxicity in those with dormant IBD [ 23 ]. This data offers encouraging insight into the outcomes of those who received radiation with dormant IBD; however, it is still generally recommended to avoid pelvic radiation, if possible, during an acute IBD flare-up.…”
Section: Discussionmentioning
confidence: 99%
“…Post-therapy follow-up was conducted regularly, focusing on the assessment of bowel and urinary function and their impact on health-related quality of life. The evaluation included the frequency of stool passage, presence of tenesmus, rectal discomfort, urinary incontinence, frequency of incontinence episodes, and the overall patient satisfaction with the treatment outcomes (12).…”
Section: Methodsmentioning
confidence: 99%
“…Following diagnosis, staging, and surgical evaluation, multiple factors must be considered to optimize patient selection for primary treatment of localized RCC with SABR. Patient history must be evaluated for factors that would potentially increase the toxicity risk of abdominal SABR, such as prior abdominal radiotherapy, inflammatory bowel disease [42], connective tissue disorders [43], or concurrent administration of certain systemic therapies [44]. Due to the unique management implications of disorders such as Von Hippel-Landau (VHL) disease, patients should be considered for genetic testing if presenting with multiple renal masses, age ≤ 46 years at diagnosis, or with a family history of RCC [20,45].…”
Section: Patient Evaluation Prior To Sabrmentioning
confidence: 99%